Upaya Peningkatan Kemampuan Numerasi Melalui Implementasi Game Based Learning Siswa Kelas V Di SDN 06 Rantau Bertuah - Lora Septiana; Efi Afnizar (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
Numeracy is students' ability to apply, apply number concepts and arithmetic operations in everyday life. Numeracy is part of an individual's ability to analyze understanding through mathematical language. So that this ability becomes the most important unit for responding to the challenges of the 21st era. The aim of the research is to determine the achievement of the numeracy ability level of class V students at SDN 06 Rantau Bertuah, Minas District, Siak Regency. The research method is PTK or Classroom Action Research with the research design model of Sthepen Kemmis and Mc. The learning model is Game Based Learning using the snake and ladder game as a learning medium. The implementation results show that in the first cycle of classroom action research, the percentage of students who completed was 53%. Meanwhile, in the second cycle of classroom action research, a percentage of 87% of students answered completely. So it can be said that the implementation of the Game based learning model using snakes and ladders media has the potential to improve the numeracy skills of class V students at SD Negeri 06 Rantau Bertuah.